Round trip to Hades in the Eastern Mediterranean tradition: visits to the underworld from antiquity to Byzantium - Ekroth, Gunnel; Nilsson, Ingela (Cultural interactions in the Mediterranean, 2018)
"The possibility of visiting the realms of the dead and yet returning alive is an idea that has fascinated people throughout time and across cultures. The European tradition goes back to Greek and Roman antiquity, represented by such famous round trips to Hades as those undertaken by Odysseus and Aeneas, but it is clear that the Graeco-Roman tradition had older Mesopotamian antecedents."--